THE QUESTION contractual liability under the contract for electricity supply - Вавженчук C. Я. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In this article an author pays attention to the separate aspects of legal nature of responsibility of participants of contractual relations in the field of supply of electric power. Attention is sparedto scientific approaches in relation to determination of civil liability, to objective and subjectcomposition of responsibility in breach of contract on the supply of electric power.